Gold Nanobipyramids as Plasmonic Sensor for Insecticide Detection in Lettuce - Iwantono, Iwantono; Saputra, Arif Darma; Nurrahmawati, Puji; Isda, Mayta Novaliza; Nafisah, Suratun; Syahputra, Romi Fadli; Morsin, Marlia (Trends in Sciences, 2024)
The application of malathion, an insecticide derived from organophosphates, raises substantial apprehensions over human health in the context of pest management in agricultural produce. The presence of a lack of specialized knowledge and the intricate nature of traditional diagnostic methods have further intensified these symptoms, resulting in significant and persistent damage to the human body. The present study aims to synthesis a gold-nanobipyramids (AuNBPs) for identifying malathion and other organophosphate pollutants, even at exceedingly low levels of detection. The AuNBPs is synthesis by the utilization of the seed-mediated growth (SMG) method. The UV-Vis spectroscopy analysis has identified 2 unique absorption peaks, specifically transverse surface plasmon resonance (t-SPR) occurring between 550 and 600 nm, and longitudinal surface plasmon resonance (l-SPR) occurring within the wavelength range of 750 to 850 nm. Additional analysis of AuNBPs reveals its capacity for notable and distinctive optical resonance, particularly in the visible and near-infrared regions of the electromagnetic spectrum. This characteristic renders AuNBPs very appropriate for the development of localized surface plasmon resonance (LSPR) sensors. The sensitivity experiments conducted on the LSPR sensor based on AuNBPs have shown compelling evidence of its capability to detect malathion and other pollutants in the AuNBPs growth solution across different concentrations. These findings highlight the sensor’s potential for efficient residue detection of malathion. This discovery underscores the significant importance of its function in safeguarding food safety and reducing the potential hazards linked to the utilization of malathion and other insecticides based on organophosphates in agricultural practices. HIGHLIGHTS The present study reports a gold-nanobipyramids (AuNBPs) synthesis using the seed-medited growth technique and characterized using a range of techniques, including UV-Vis spectroscopy and XRD The plasmonic sensor demonstrated heightened sensitivity to malathion, as evidenced by a rise in values corresponding to the concentration of the residual solution The intensity of AuNBP in the presence of malathion was significantly increased compared to that in deionized water, suggesting that AuNBP exhibits a strong and effective reaction to the presence of malathion residue GRAPHICAL ABSTRACT